Gender and climate risk management: evidence of climate information use in Ghana - Tetteh Partey, Samuel (International Crops Research Institute for the Semi-Arid Tropics, 2019)
Presented by Samuel Tetteh Partey (International Crops Research Institute for the Semi-Arid Tropics [ICRISAT]) on January 23, 2019 as part of the webinar 'Guidelines and good practices for achieving gender equality outcomes through climate services'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS).